2021
DOI: 10.3389/fmicb.2021.781797
|View full text |Cite
|
Sign up to set email alerts
|

Extended Bacteria Culture-Based Clustering Identifies a Phenotype Associating Increased Cough and Enterobacterales in Stable Chronic Obstructive Pulmonary Disease

Abstract: Chronic obstructive pulmonary disease (COPD) is a chronic inflammatory lung disease characterized by airflow limitation. This chronic respiratory disease represents the third leading cause of death worldwide. Alteration of the airway microbiota has been reported to be associated with exacerbation frequency in COPD, but its role on the symptoms in patients at stable state is still incompletely described. This study aimed to determine whether bacteria isolated in sputum can be associated with the clinical featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Patients with mild to severe COPD were included prospectively in the RINNOPARI cohort (Recherche et INNOvation en PAthologie Respiratoire Inflammatoire; University Hospital of Reims, France; NCT02924818) as described previously 6 The regional ethics committee approved the study (Comité de Protection des Personnes-Dijon EST I, no. 2016-A00242 -49).…”
Section: Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with mild to severe COPD were included prospectively in the RINNOPARI cohort (Recherche et INNOvation en PAthologie Respiratoire Inflammatoire; University Hospital of Reims, France; NCT02924818) as described previously 6 The regional ethics committee approved the study (Comité de Protection des Personnes-Dijon EST I, no. 2016-A00242 -49).…”
Section: Patientsmentioning
confidence: 99%
“…Previous studies performed in a stable state identified associations between the sputum microbiome and COPD phenotypes. [4][5][6] Associations with COPD inflammatory phenotypes including eosinophils have been recently investigated, suggesting that different profiles of bacteria phyla might be associated with different profiles of inflammation: low sputum eosinophil count in the presence of potential pathogenic microorganism (PPM), 7,8 more diverse respiratory microbiome in subjects with BEC ≥2%. 9 However, the relationships between BEC and airway microbiota and its clinical implications remain to be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using a combination of multiple culture conditions and media, Whelan et al showed that an average of 82.13% of bacterial OTUs from sputum of cystic fibrosis patients can be cultured [44] . Through a comprehensive cultivation effort, Muggeo et al found an enrichment of Enterobacterales was associated with deteriorated clinical symptom in COPD patients [45] . Sun et al have characterized the lung and oral microbiota using culturomics and 16S rRNA gene sequencing and found site and pathology-dependent alterations in patients with lung cancer [46] .…”
Section: The Multi-omics For the Lung Microbiomementioning
confidence: 99%
“…In the past, based on culture-dependent techniques, it was thought that the lungs of healthy individuals were sterile. The primary tool for identifying pathogens responsible for lung infections was bacteriology-based culture ( Muggeo et al, 2021 ). With advances in next-generation sequencing technology, researchers have found that, even in healthy individuals, the lungs are not as sterile as was once thought.…”
Section: Introductionmentioning
confidence: 99%